LncRNAs: The Regulator of Glucose and Lipid Metabolism in Tumor Cells - Lu, Wei; Cao, Fenghua; Wang, Shengjun; Sheng, Xiumei; Ma, Jie (Frontiers in Oncology, 2019)
Metabolism is a complex network of regulatory systems. Cells often alter their metabolism in response to the changes of their environments. These adaptive changes are particularly pronounced in tumor cells, known as metabolic reprogramming. Metabolic reprogramming is considered to be one of the top ten characteristics of tumor cells. A large number of experimental studies have shown that long non-coding RNAs (lncRNAs) play an important role in glucolipid metabolism of tumor cells. The current review briefly introduces the regulation effect of lncRNAs on glucose and lipid metabolism of tumor cells, and the significance of lncRNAs-mediated metabolism in tumor therapy, hoping to provide new strategies for clinical targeting tumor therapy.